2006
DOI: 10.1073/pnas.0603044103
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial TARP is a bacterial nucleator of actin

Abstract: Chlamydia trachomatis entry into host cells results from a parasitedirected remodeling of the actin cytoskeleton. A type III secreted effector, TARP (translocated actin recruiting phosphoprotein), has been implicated in the recruitment of actin to the site of internalization. To elucidate the role of TARP in actin recruitment, we identified host cell proteins that associated with recombinant GST-TARP fusions. TARP directly associated with actin, and this interaction promoted actin nucleation as determined by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
232
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(240 citation statements)
references
References 42 publications
8
232
0
Order By: Relevance
“…Chlamydiae manipulate cytoskeletal structures to facilitate entry (Jewett et al, 2006), redirect vesicular traffic (Scidmore et al, 1996a), and maintain chlamydia-filled inclusions in close proximity to the nucleus and other organelles (Grieshaber et al, 2003). The chlamydiainduced alteration of a-adducin and Raf-1 distribution described in this report may influence the interaction of these proteins with downstream substrates, perhaps contributing to chlamydial development and growth.…”
Section: Discussionmentioning
confidence: 97%
“…Chlamydiae manipulate cytoskeletal structures to facilitate entry (Jewett et al, 2006), redirect vesicular traffic (Scidmore et al, 1996a), and maintain chlamydia-filled inclusions in close proximity to the nucleus and other organelles (Grieshaber et al, 2003). The chlamydiainduced alteration of a-adducin and Raf-1 distribution described in this report may influence the interaction of these proteins with downstream substrates, perhaps contributing to chlamydial development and growth.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from TARP, a protein able to interact with actin and probably involved in chlamydial invasion (41), little is known about the roles of these proteins in Chlamydia biology. CT733/TC0106 is, thus far, an uncharacterized protein.…”
Section: Discussionmentioning
confidence: 99%
“…Still other bacterial pathogens use virulence factors, such as ActA from Listeria, which encodes multiple PRMs to manipulate the eukaryotic nucleating factor Arp2/3 (39,40). The TARP protein from Chlamydia contains only one WH2 domain and is less potent than VopL in in vitro actin assembly assays (41). In addition, a family of bacterial G protein mimics have been identified that replicate signaling properties of Rho-like GTPase in manipulating the actin cytoskeleton (42).…”
Section: Discussionmentioning
confidence: 99%